(untitled) (Bangladesh Journal of Bioethics, 2018)
Welcome to all readers of the BJB Vol 9 issue 3, 2018! The BJB team together with authors, reviewers and well- wishers have contributed their all-out support to bring out this issue despite many challenges. This issue spans several topics of Bioethics beginning from complementary feeding patterns, ethical beliefs and vaccine, the regulatory documents related to pharmaceutical promotion in Bangladesh and Intimate Partner Violence. All these topics are very important for Bangladesh as well other countries.